KAJIAN AKADEMIK PENYUSUNAN RANCANGAN PERATURAN DAERAH TENTANG SISTEM MANAJEMEN TRANSPORTASI DI KABUPATEN SUMBAWA - Iwan Haryanto; Tri Satriawansyah; A Ardiyansyah; Ana Merdekawaty (Fakultas Ekonomi dan Manajemen, 2021)
This study aims to provide a scientific and academic basis in making regulations regarding the transportation management system in Sumbawa Regency in the form of an academic text. To examine this study using empirical legal research methods with data collection using observation, document studies and interviews. The results obtained in this study are an empirical review of the number of groups that are still dependent on public transportation, but are not balanced with the provision of adequate public transportation, especially in terms of the feasibility of public transportation itself. Several factors make people reluctant to use public transportation, including security that is not guaranteed, facilities that are not feasible and are not environmentally friendly. The results of the evaluation and analysis of laws and regulations related to the transportation management system can be divided into 2, namely attribute regulations and delegation regulations. The drafting of a regional regulation on transportation management systems is based on a philosophical basis, a sociological basis and a juridical basis.